Bacillus pumilus SAFR-032 Genome Revisited: Sequence Update and Re-Annotation - Stepanov, Victor G. (PLoS One, 2016)
Bacillus pumilus strain SAFR-032 is a non-pathogenic spore-forming bacterium exhibiting an anomalously high persistence in bactericidal environments. In its dormant state, it is capable of withstanding doses of ultraviolet (UV) radiation or hydrogen peroxide, which are lethal for the vast majority of microorganisms. This unusual resistance profile has made SAFR-032 a reference strain for studies of bacterial spore resistance. The complete genome sequence of B. pumilus SAFR-032 was published in 2007 early in the genomics era. Since then, the SAFR-032 strain has frequently been used as a source of genetic/genomic information that was regarded as representative of the entire B. pumilus species group. Recently, our ongoing studies of conservation of gene distribution patterns in the complete genomes of various B. pumilus strains revealed indications of misassembly in the B. pumilus SAFR-032 genome. Synteny-driven local genome resequencing confirmed that the original SAFR-032 sequence contained assembly errors associated with long sequence repeats. The genome sequence was corrected according to the new findings. In addition, a significantly improved annotation is now available. Gene orders were compared and portions of the genome arrangement were found to be similar in a wide spectrum of Bacillus strains.